Conflicts and Response Strategies in Sexuality Education Practices by Guest Educators in China: Focusing on Narratives - Shixing LI; Xiaowen Tu (Master Program of Health Promotion Faculty of Public Health Diponegoro University, 2026)
ABSTRACTBackground: The sexual environment surrounding young people in China has been deteriorating. Although the government has issued policies to promote school-based sexuality education, implementation remains problematic. However, due to the weak institutional positioning of these guest educators and insufficient policy safeguards, they frequently encounter conflicts. While previous research has primarily focused on regular school teachers and institutional barriers, guest educators in China remain an insufficiently theorized category of practitioners. To address this gap, this study examines the conflicts guest educators face, analyzes how they respond, and proposes a Motivation-Conflict-Strategy model.Method: This qualitative study recruited eight guest educators affiliated with the Family Sexuality Education Subcommittee of the Chinese Sexology Association. Data were collected through semi-structured interviews and analyzed using thematic analysis.Result: The analysis yielded a Motivation-Conflict-Strategy model. Guest educators exhibit strong motivation to implement sexuality education, grounded in personal experiences, professional experiences, and value orientations. Yet, during implementation, they face multiple conflicts: (a) conflicts rooted in value frictions, (b) personal dilemmas, (c) conflicts stemming from institutional instability and devaluation, and (d) conflicts arising from positional vulnerability. Crucially, these strategies in turn reshape educators' motivation, making the model a recursive Motivation-Conflict-Strategy-Motivation loop rather than a linear sequence. The “Motivation-Conflict-Strategy” model reconceptualizes sexuality education in China as a dynamic interplay among institutional structures, sociocultural norms, and individual agency, highlighting the urgent need to establish institutional safeguards for diverse practitioners and to develop specialized sexuality education programs at teacher training colleges.Keywords: Sexuality education, Guest educator, Conflict, Response strategies